2019
DOI: 10.1108/9781789737516
|View full text |Cite
|
Sign up to set email alerts
|

Central Bank Policy: Theory and Practice

Abstract: The book rigorously discusses the theories, empirical studies and practices of international financial and monetary policy in emerging market economies, including Indonesia. Furthermore, the book is an invaluable policymaking input for the central bank and government, teaching material for lecturers and students as well as an important reference for scientific development in academia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 0 publications
0
29
0
3
Order By: Relevance
“…A growing body of literature suggests numerous technical approaches to define the extent of credible monetary policy. Warjiyo and Juhro (2019) define monetary policy credibility as the deviation of actual and targeted inflation. The larger the deviation of actual inflation from the target, the less credible the monetary policy.…”
Section: Empirical Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of literature suggests numerous technical approaches to define the extent of credible monetary policy. Warjiyo and Juhro (2019) define monetary policy credibility as the deviation of actual and targeted inflation. The larger the deviation of actual inflation from the target, the less credible the monetary policy.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Equation (11) implies that tightening monetary policy (increased interest rate) leads to larger pessimism, and risk-averse behaviour reduces demand for credit, high loan loss provisions and a higher probability of the bubble to burst (Warjiyo & Juhro, 2019). In addition, higher interest rates imply Ó 2020 The Economic Society of Australia higher borrowing costs.…”
Section: Financial Instability Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1980, capital flows have been increasing and have been through several events, such as Asian Financial Crises (AFC) in 1998 and Global Financial Crises (GFC) in 2008. The size of capital flows can be counted by percentage to the GDP as table 1 below 1980-1989 1990-1999 2000-2007 2008 Warjiyo & Juhro (2016).…”
Section: Capitalmentioning
confidence: 99%
“…Policy Mix: Relationship between risk on Price and Financial System StabilityIt is necessary when Bank Indonesia formulates a policy mix to consider risk assessment on the price and financial system stability Warjiyo and Juhro (2017). have suggested that there are four combination possibilities of risk of the price stability and financial system stability, which could be a general guideline for implementing the policy mix.In a condition where the price stability is stable (inflation is in the band's target) and has a low credit growth (Quadrant I), policy makers can be accommodative and accommodate macroprudential and monetary policies.…”
mentioning
confidence: 99%